Spatial distribution of sediment pollution in the Khajeh Kory River using Kriging and GIS (2014)
The aim of this research was to study of sediment pollution conditions in the river bed of Khajeh Kory, which passes from the southern border of the Caspian Sea in Astara City. To determine the pollution of river bed sediment along the route, from the river source in the heights to estuary in the Caspian sea, sampling was conducted at 10 stations. Afterward, each sample was divided into two groups based on size (63 µm and 63 µm). The concentration of heavy metals Cu, Cd, Co, Zn, Pb, Ni, Fe, and Mn in each group was measured using ICP-OES. In the next stage, the enrichment of samples was determined by normalization with aluminum. The data were then interpolated using the Kriging method and various models (including spherical, circular, exponential, Gaussian) were fitted to the data, and the best method was selected using the Cross Validation method. Using the obtained enrichment outcomes, an information layer was produced for each element in the GIS environment utilizing the Kriging method. The layers were aggregated and the compiled layer was  classified into 4 layers again. Using this method, the length of the river from its source to the sea estuary was characterized based on the contamination of heavy metals, and contaminated and unpolluted areas in river sediments could be observed. The source of this pollution, either natural or manmade, was revealed through this method. ResumenEl objeto de esta investigación fue estudiar las condiciones de contaminación sedimentaria en el lecho del río Khajeh Kory, que se extiende desde el borde sur del Mar Caspio en la ciudad de Astara. Para determinar la contaminación del lecho sedimentario, se recolectaron muestras en 10 estaciones establecidas entre la fuente del río en sus partes altas hasta los estuarios en el Mar Caspio. Después, cada muestra fue dividida en dos grupos de acuerdo con el tamaño (63 µm and 63 µm). La concentración de metales pesados Cu, Cd, Co, Zn, Pb, Ni, Fe y Mn en cada grupo se midió con la técnica ICP-OES. En la siguiente etapa, se determinó el enriquecimiento de las muestras por la normalización con aluminio. Los datos se interpolaron luego con el método Kriging y varios modelos (incluidos el esférico, el circular, el exponencial, el gaussiano) se ajustaron a la información y se seleccionó el mejor método a través de la Validación Cruzada. Con los resultados obtenidos del enriquecimiento se produjo una capa de información para cada elemento en el ambiente GIS a través del método Kriging. Las capas fueron agregadas y la compilación de estas se clasificó nuevamente en otras cuatro capas. De esta forma se caracterizó el río a lo largo, desde su nacimiento hasta el estuario marino, con base en la contaminación de metales pesados y se pudo distinguir entre las zonas contaminadas y las áreas limpias en sedimentos. Las fuentes de esta contaminación, sean naturales o humanas, también se identificaron con este método.